Improving Cervical Screening in Trans and Gender-Diverse People. Issue 1 (January 2022) - Kerr, Lucille; Fisher, Christopher M.; Jones, Tiffany
Abstract : Background: Trans and gender-diverse people with a cervix experience difficulties accessing cervical cancer screening because of structural, interpersonal, and individual barriers. Objective: The aim of this study was to explore issues with cervical cancer screening participation, awareness, and healthcare provider recommendation for trans and gender-diverse people. Methods: A national Australian survey was conducted in 2018 to 2019. Participants included 196 trans and gender-diverse people with a cervix. Data were analyzed using descriptive and multiple regression analyses. Two awareness items related to cervical cancer screening, healthcare provider recommendation, and cervical cancer screening participation were assessed. Four variables associated with cervical cancer screening were included in the regression: age, healthcare provider recommendation, like for body, and gender. Results: The sample was young; half (52.6%) were aged 20 to 24 years. Almost half (44.6%) had never had a healthcare provider recommend cervical cancer screening to them. Around half (48.0%) had never participated, with 21.9% reporting that they are regular screeners. More than a quarter (27.5%) of people who had screening had an abnormal result. The most common reasons for not participating in screening were that it is emotionally traumatic for them (55.3%) and inability to find a healthcare provider with whom they are comfortable (38.3%). Conclusions: Trans and gender-diverse Australians with a cervix are unlikely to be regular participants in cervical cancer screening. To continue reducing cervical cancer rates, healthcare providers must address underscreening in this community. Implications for Practice: Gender diversity training needs to be provided to healthcare providers. In addition, healthcare providers need to promote participation in cervical screening in this trans and gender-diverse community.